Water quality status of the Serayu Watershed (DAS) using the STORET method approach - Hidayati, Nuning Vita; Condro, Abi; Jatmoko, Bambang Eko; Fikriyya, Nabela; Junaidi, Teuku; Hastuti, Dewi Wisudyanti Budi; Firdaus, Abdul Malik; Raharja, Ferry Cahya (Universitas Malikussaleh, 2025)
The Serayu River Basin (DAS) spans 180 km and traverses several districts in Central Java, including Wonosobo, Banyumas, Banjarnegara, Cilacap, and Purbalingga. Significant pollution has been observed in the Serayu River Basin, with the primary sources of pollution being agriculture, industry, and community activities. The objective of this investigation is to evaluate the Serayu River Basin's condition in relation to the STORET method and Class I, II, III, and IV water quality standards, as well as physical and chemical parameters. Ex situ analysis of water samples was implemented through purposive random sampling in the survey methodology. Class I pollution levels in the Serayu River Basin are classified as Category D, which denotes substantial pollution, according to the STORET method. Class II is classified as Category C, which denotes moderate pollution, as indicated by a STORET index value of -26. Several research locations exhibit water parameters that exceed the quality standards, including pH, DO, COD, phosphate, and ammonia. In order to preserve the purity and condition of the Serayu River Basin, it is necessary for all stakeholders, including the community, to participate. Furthermore, the management of the Serayu Watershed necessitates the implementation of control strategies or efforts. Keywords: Basin; River pollution; Serayu; STORET; Water Quality